2008
DOI: 10.1149/1.2844288
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Epitaxial Fe and Ni Thin Films Grown on n-AlGaAs(001) Using Electrodeposition

Abstract: We report epitaxial growth of body-centered cubic Fe and face-centered cubic Ni thin films on n-type AlGaAs͑001͒ substrates using electrochemical deposition with the cubic axes of Fe oriented parallel to the substrate lattice while the Ni is rotated in-plane 45°. The magnetic properties in either case are dominated by the fourfold crystalline anisotropy, a high remanence, and saturation magnetization values similar to bulk properties. The growth of such ferromagnetic contacts on AlGaAs might find applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Plan-view transmission electron microscopy ͑TEM͒ investigations found that nucleation and coalescence of Fe films electrodeposited under similar condition occurs within 1 s. 18 The linear thickness vs time behavior reported here is that expected for a galvanostatic process. 29 The deviation from this linear behavior at longer times is likely related to the depletion of Fe ions and the…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Plan-view transmission electron microscopy ͑TEM͒ investigations found that nucleation and coalescence of Fe films electrodeposited under similar condition occurs within 1 s. 18 The linear thickness vs time behavior reported here is that expected for a galvanostatic process. 29 The deviation from this linear behavior at longer times is likely related to the depletion of Fe ions and the…”
Section: Resultssupporting
confidence: 68%
“…17 There is also a recent report of the growth of epitaxial Fe and Ni on AlGaAs. 18 In all cases these metals were electrodeposited from conventional, highly acidic electrolyte to inhibit the formation of oxides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrodeposition of epitaxial Fe films on GaAs has been proposed as an efficient alternative to physical deposition methods. [8][9][10][11][12][13][14] The low-energy character of the electrodeposition technique means that interface intermixing 15 is largely avoided. In general, Fe deposition on GaAs proceeds via island nucleation, coalescence, and subsequent film growth, which for electrodeposition is typically at rates of 2-6 nm/s, perhaps 100 times faster than MBE.…”
mentioning
confidence: 99%
“…Furthermore, at the point of coalescence, the thickness lies above 20 nm for electrodeposition, 10 in stark contrast to about 3 atomic layers for MBE. 16 Therefore, most studies on electrodeposited Fe on GaAs [8][9][10][11][12][13] have focused on the fabrication of films of several 100 nm, and the structural, magnetic 12 and spin transport characterization 13 of these. Recently, we demonstrated that epitaxial Fe nanocuboids can be achieved when the deposition is stopped prior to coalesce of the nuclei in a lower-concentration electrolyte with reduced deposition rate.…”
mentioning
confidence: 99%